A mood state‐specific interaction between kynurenine metabolism and inflammation is present in bipolar disorder. (30th August 2019) - van den Ameele, Seline; van Nuijs, Alexander LN; Lai, Foon Yin; Schuermans, Jeroen; Verkerk, Robert; van Diermen, Linda; Coppens, Violette; Fransen, Erik; de Boer, Peter; Timmers, Maarten; Sabbe, Bernard; Morrens, Manuel
Abstract: Objectives: Cytokines are thought to contribute to the pathogenesis of psychiatric symptoms by kynurenine pathway activation. Kynurenine metabolites affect neurotransmission and can cause neurotoxicity. We measured inflammatory markers in patients with bipolar disorder (BD) and studied their relation to kynurenine metabolites and mood. Methods: Patients with BD suffering from an acute mood episode were assigned to the depressive (n = 35) or (hypo)manic (n = 32) subgroup. Plasma levels of inflammatory markers [cytokines, C‐reactive protein] and kynurenine metabolites [tryptophan (TRP), kynurenine (KYN), 3‐hydroxykynurenine (3‐HK), quinolinic acid (QA), kynurenic acid (KYNA)] were measured on 6 time points during 8 months follow‐up. Biological marker levels in patients were compared to controls (n = 35) and correlated to scores on mood scales. Spearman correlations and linear mixed models were used for statistical analysis. Results: Twenty patients of the manic subgroup, 29 of the depressive subgroup, and 30 controls completed the study. The manic subgroup had a rapid remission of mood symptoms, but in the depressive subgroup subsyndromal symptoms persisted. No differences in inflammation were found between groups. A strong correlation between tumor necrosis factor‐ α and KYN, KYN/TRP, 3‐HK and QA ( ρ  > 0.60) was specific for the manic group, but only at baseline (during mania). The depressive subgroup had a lower neuroprotective ratio (KYNA/3‐HK, P  = .0004) and a strong association between interferon‐y and kynurenine pathway activation ( P  < .0001). KYNA was low in both patient groups versus controls throughout the whole follow‐up ( P  = .0008). Conclusions: Mania and chronic depressive symptoms in BD are accompanied by a strong interaction between inflammation and a potentially neurotoxic kynurenine metabolism.